The influence of pulsatile preservation in kidney transplantation from non-heart-beating donors. - Moustafellos, P; Hadjianastassiou, V; Roy, D; Muktadir, A; Contractor, H; Vaidya, A; Friend, P (2007)
Continuous hypothermic pulsatile perfusion (CHPP) may offer improved early function compared with cold static perfusion (CSP) for heart-beating cadaveric donors. With an expanding pool of donors, ie, non-heart-beating donors (NHBD), we present our preliminary results with the use of CHPP compared with CSP to preserve kidney grafts retrieved from NHBD. Eighteen consecutive locally procured cadaveric kidneys from NHBD were preserved using CHPP using UW machine perfusion solution in the Life Port kidney transporter. Perfusion parameters were measured serially during pulsatile perfusion. This group was compared with 18 NHBD cadaveric kidneys preserved with CSP. No organs were lost due to faulty technique of preparation or preparation of pulsatile perfusion. Immediate renal function was observed in 13 cases (72.2%). In CSP in NHBD, we had 16 cases with delayed graft function (88.8%). These early results show that the use of pulsatile perfusion to preserve kidneys from NHBD may be associated with improved early outcomes. Longer follow-up is required to answer the more important question as to whether it offers long-term improvements that justify the extra cost and complexity.